2019
DOI: 10.1128/mbio.02591-19
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Metabolism Activates Aryl Hydrocarbon Receptor-Mediated Pathway To Promote HIV-1 Infection and Reactivation

Abstract: Cellular metabolic pathways that are altered by HIV-1 infection may accelerate disease progression. Dysfunction in tryptophan (Trp) metabolism has been observed clinically in association with accelerated HIV-1 pathogenesis, but the mechanism responsible was not known. This study demonstrates that Trp metabolites augment the activation of aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor, to promote HIV-1 infection and transcription. These findings not only elucidate a previously unapprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 81 publications
(115 reference statements)
1
24
0
Order By: Relevance
“…Moreover, the binding of AHR with Tat viral protein facilitates the recruitment of positive transcription factors to viral promoters. These findings elucidate a previously unappreciated mechanism through which cellular Trp metabolites affect HIV pathogenesis, and also suggest that AHR signaling may be targeted to modulate HIV-1 infection ( 115 ).…”
Section: Ahr and Viral Infectionssupporting
confidence: 52%
See 1 more Smart Citation
“…Moreover, the binding of AHR with Tat viral protein facilitates the recruitment of positive transcription factors to viral promoters. These findings elucidate a previously unappreciated mechanism through which cellular Trp metabolites affect HIV pathogenesis, and also suggest that AHR signaling may be targeted to modulate HIV-1 infection ( 115 ).…”
Section: Ahr and Viral Infectionssupporting
confidence: 52%
“…Unusual high levels of Kyn have been detected in association with accelerated HIV-1 pathogenesis, but the molecular mechanism behind this observation remains unclear. However, it was recently reported that AHR is activated by Trp metabolites to favor HIV-1 infection and reactivation ( 115 ), suggesting a novel role for AHR in AIDS. AHR directly binds to the HIV-1 5′ long terminal repeat (5′-LTR) to activate viral transcription.…”
Section: Ahr and Viral Infectionsmentioning
confidence: 99%
“…Moreover, rats with decreased intake of tryptophan had higher running performance (Yamamoto & Newsholme, 2003). Trp metabolites acting on the metabolic crossroad interconnecting different organs exert various beneficial effects (Le Floc'h et al., 2011; Roager & Licht, 2018) in a multiple of disorders, including central nervous system disorders, autoimmune diseases, and cancer (Zhou et al., 2019). Under inflammatory conditions, most Trp is diverted to produce Kyn and its metabolites kynurenine acid (KYNA) (Keszthelyi et al., 2012) with neuroprotective roles (Lim et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of sepsis and septic shock was defined in accordance with the Third International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3) 25 . The septic patients and healthy controls who met the exclusion criteria were excluded according to our previous studies 3 , 26 . The clinical variables such as gender, age, blood microbiological cultures, source of infection, Sequential Organ Failure Assessment (SOFA) and APACHE II score were collected.…”
Section: Methodsmentioning
confidence: 99%